Natural and engineered resistance to plant viruses : Part II. - Carr, John (Advances in virus research, 2010)
Viruses are a huge threat to agriculture. In the past, viruses used to be controlled using conventional methods, such as crop rotation and destruction of the infected plants, but now there are more novel ways to control them. This volume focuses on topics that must be better understood in order to foster future developments in basic and applied plant virology. These range from virus epidemiology and virus/host co-evolution and the control of vector-mediated transmission through to systems biology investigations of virus-cell interactions. Other chapters cover the current status of signalling i.